CHOLESTATIC LIVER FIBROSIS IN A RAT MODEL OF BILE DUCT LIGATION: EVALUATING BIOCHEMICAL VERSUS HISTOPATHOLOGICAL CHANGES - Mohamed, Hoda E.; Elswefy, Sahar E.; Rashed, Laila A.; Younis, Nahla N.; Shaheen, Mohamed A.; Ghanim, Amal M. H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Bile duct ligation (BDL), chronic liver injury model, was extensively used in studying mechanisms of fibrogenesis and antifibrotic agents. Considering the liver regenerative capacity and the diverse results from BDL, the present study aimed to evaluate the biochemical and histopathological changes over 10 weeks following BDL assessing if BDL-induced changes remain in a deterioration state or improve at a certain stage. Methods: Sham operation and BDL were conducted in Male Wistar rats. Serum AST, ALT, total bilirubin and albumin and hepatic hydroxyproline (HYP), reduced glutathione (GSH) and malondialdehyde (MDA) were measured in sham-operated (n=3) and BDL-rats (n=6) at 0, 1, 2, 4, 6, 8 and 10 weeks following operation. Liver tissue was also processed for histopathological analysis (H&E and Sirus red staining). Results: Progressive liver injury (H&E) and collagen deposition (Sirus red and HYP) in BDL-rats were observed starting from the first week post-operation and reached their maximum with early signs of cirrhosis on the 10th week of BDL. Severe and sustained cholestatic injury appeared in 2 weeks (increased ALT, AST, bilirubin along with decreased albumin (P<0.001) compared to sham-operated rats). AST peaked on first week, however, bilirubin, ALT and MDA peaked on the 4th week (P<0.001) then gradually decreased compared to their peaks. Conclusion: The relative improvement in liver function/cholestasis following their peaks in BDL model despite progression of fibrosis and hepatic injury require investigators using this model to consider not only biochemical, but also histopathological findings to guarantee an accurate interpretation of their results. Â 